Paper Folding Art Activities in Early Childhood Learning - Satrial, Ardi; Adriyani, Sylva; Rahmi, Azvi; Indria, Anita; Utami, Rahmi Dwi (Journal of Islamic Early Childhood Education, 2024)
The problem in writing this thesis is the delay in the development of fine motor skills in children aged 5-6 years. Based on this, the author is interested in further research, namely "How is the Implementation of Paper Folding Art for Children Aged 5-6 Years?" The purpose of this study is (1) to find out and understand the art of paper folding (2) to find out the supporting and inhibiting factors in this paper folding art activity. This type of research is qualitative research with teacher data sources with interview, observation, and documentation instruments and to draw conclusions. Based on the results of the research conducted, it can be concluded that paper folding activities are very rarely done so that children's fine motor skills in this activity have not been achieved as expected (3) Supporting and inhibiting factors when carrying out this paper folding activity process, namely, seen from the supporting factors of complete tools and materials and adequate facilities, the presence of enthusiasm, stimulus and motivation from teachers and parents. while the inhibiting factors are limited time and the condition of children who are difficult to direct, children who do not follow the rules during the activity because they are still young and in this folding activity there are children who are naughty and disturb friends so that they lack concentration.